Bird Community Structure And Diversity In Peninsular Malaysia - Azman, Nur Munira (2017)
Peninsular Malaysia has rich and diverse flora and fauna. Much of these have yet to be documented. The avifauna is an important group that has received little attention, ecologically in this country. Different approaches of diversity measurements are presented in this thesis in order to evaluate the bird diversity in natural and man-made habitats. The objectives of this study are to determine the current bird species composition and diversity, to analyse β-diversity of birds, to investigate patterns of rarity among birds in natural habitats, and to study the contribution of rice fields to the bird diversity in Peninsular Malaysia by using multiple diversity measurements.